Developing a sensitive, high-throughput tool for rapid detection of agronomically important seed-borne pathogens of tomato - Carmichael, Deborah Jo (My University, 2013)
The limited specificity, sensitivity and multiplex capacity of detection techniques currently available for important seed-borne pathogens of tomato is a significant risk for the global tomato trade and production industry. These pathogens can be associated with seed at low concentrations but, due to their highly virulent nature, these low levels can be sufficient to infect germinating seedlings and spread to neighbouring plants and fields, potentially causing epidemics and economic losses. In this study, detection techniques currently available for phytodiagnostics were evaluated for the capacity to accurately detect and identify five agronomically important seed-borne pathogens of tomato: Pepino mosaic virus (PepMV), Tomato mosaic virus (ToMV), Clavibacter michiganensis subsp. michiganensis (Cmm), Xanthomonas campestris pv. vesicatoria and Pseudomonas syringae pv. tomato. A prototype diagnostic microarray was also designed in an attempt to develop a tool that could simultaneously detect these five seed-borne pathogens from a single sample. Viral detection based on serological techniques was rapid, accurate and reliable but only detected a single pathogen per assay and required supplementary bioassays to indicate the viability of detected viral pathogens. Selective media plating for bacterial detection demonstrated unreliable recovery of targeted bacteria from infected seed and leaf samples and required supplementary tests to validate the identity of presumptive positives. Assays were lengthy, laborious and sometimes too ambiguous for accurate diagnosis of bacterial pathogens. Nucleic acid-based technologies demonstrated improved sensitivity and specificity for detection of targets from pure culture, leaf and seed extracts, compared to conventional and serological methods, yet also required supplementary bioassays or media assays to validate the viability of detected pathogens. Amplification efficiency however, was affected by the presence of PCR inhibitors and despite positive detection, variable banding intensity in electrophoretic analysis of amplified products necessitated the use of reference cultures to validate diagnosis. The developed microarray incorporated 152 pathogen-specific and control probes to facilitate diagnosis and taxonomic classification of detected pathogens. The array was challenged with pure culture extracts of the five target pathogens, selected related and non-target, unrelated pathogens of tomato. Positive detection of each of the pathogens was demonstrated but the production of hybridisation signals was highly variable and extremely sensitive to minor technical differences. Each of the five pathogens were successfully detected in combination proving that different classes of seed-borne pathogens could be detected from a single sample using the developed microarray. This prototype microarray has good potential for phytodiagnostic screening of the five targeted pathogens, and further validation, optimisation and extension for testing tomato seed samples may facilitate incorporation of this array into standard diagnostic protocols.
Keywords: Tomatoes.; Seed-borne plant diseases.; Plant viruses.; Tomatoes - Diseases and pests.